Conductive resin composition, electromagnetic wave shielding layer, and electronic component
By using a conductive resin composition containing silver particles, combined with components such as epoxy resin and carbon particles, an electromagnetic wave shielding layer is formed, and the problem of deterioration of the electromagnetic wave shielding layer in the prior art is solved, and excellent Adhesion and durability and efficient electromagnetic wave shielding effect.
Patent Information
- Application Number
- CN202380052478.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-14
AI Technical Summary
The existing electromagnetic wave shielding spraying agent deteriorates over time under high temperature and high humidity environments, resulting in a decrease in adhesion.
Using a conductive resin composition containing silver particles, the pressurized elastic modulus EIT calculated by the load-displacement curve obtained by the nanoindentation test is 10 to 20 GPa. Combined with components such as epoxy resin and carbon particles, an electromagnetic wave shielding layer is formed. .
It achieves excellent adhesion and durability in high temperature and high humidity environments, and provides efficient electromagnetic wave shielding effect.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive resin composition, an electromagnetic wave shielding layer and an electronic component. Background Art
[0002] Electronic components such as power amplifiers, Wi-Fi / Bluetooth modules, and flash memory are installed on the substrates of electronic devices such as mobile phones, smartphones, laptops, and tablet terminals. Such electronic components may malfunction due to electromagnetic waves from the outside. In addition, conversely, electronic components may also become a source of electromagnetic noise and cause malfunctions of other electronic components.
[0003] In the field of electronic devices, the development of highly integrated technologies such as system-on-chip (SoC), system-in-package (SiP), and multi-chip module (MCM) that integrate multiple components into one component continues to advance, and electronic devices are becoming increasingly smaller and thinner. As electronic devices become smaller and thinner, the need to protect against electromagnetic interference (hereinafter referred to as "EMI") between components such as baseband components, radio frequency (RF) components, wireless components, analog devices, and power management components is increasing.
[0004] Furthermore, in order to protect electronic components mounted on substrates, studies have been conducted to form an electromagnetic wave shielding layer on the surface of the electronic components to block electromagnetic waves, and various materials have been studied.
[0005] For example, conductive particles such as silver and copper have low electrical resistance and are incorporated into conductive inks used in the manufacture of electronic circuits, coating agents used to form shielding layers for shielding electromagnetic waves in electronic components, etc. For example, Patent Document 1 discloses a conductive ink that does not contain a polymer or resin binder but contains nanosilver particles and an adhesion promoter.
[0006] In addition, Patent Document 2 discloses a technique for spraying a coating agent on the surface of an electronic component.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application No. 2014-529674
[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-143225 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, the conventional spray coating agent for forming the electromagnetic shielding layer deteriorates over time under a high temperature and high humidity environment, and thus the adhesion after the reliability test may be reduced.
[0013] Therefore, an object of the present invention is to provide a conductive resin composition capable of forming an electromagnetic shielding layer having a high electromagnetic shielding effect and excellent adhesion after a reliability test.
[0014] Means for solving problems
[0015] Means for solving the above-mentioned problems are as follows, and the present invention includes the following aspects.
[0016] [1]
[0017] A conductive resin composition comprising silver-containing particles as component (A) and at least one of a thermosetting resin or a thermoplastic resin as component (B), wherein the conductive resin composition has an indentation elastic modulus E obtained from a load-displacement curve obtained by a nanoindentation test according to the following steps. IT It is 10~20GPa.
[0018] [step]
[0019] (1) A conductive resin composition was applied onto a slide glass and heated at 200° C. for 20 minutes to form a coating film having a thickness of 50 μm to obtain a test piece.
[0020] (2) A load was applied to the coating surface of the test piece obtained in (1) using a Bosch indenter for 10 seconds until the maximum load reached 200 mN, the maximum load was maintained for 10 seconds, and then the load was removed for 10 seconds. A nanoindentation test was performed under these conditions to obtain a load-displacement curve.
[0021] [2]
[0022] The conductive resin composition according to [1], wherein the component (A) comprises silver particles having an average particle diameter of 100 nm to 350 nm.
[0023] 〔3〕
[0024] The conductive resin composition according to [1] or [2], wherein the component (B) contains an epoxy resin.
[0025] [4]
[0026] The conductive resin composition according to any one of [1] to [3], wherein the component (B) comprises an epoxy resin having a flexible skeleton.
[0027] 〔5〕
[0028] According to the conductive resin composition described in [4], the above-mentioned epoxy resin containing a soft skeleton contains at least one soft skeleton selected from a polyoxyalkylene skeleton, a polyethylene glycol skeleton, a polypropylene glycol skeleton, a polyether skeleton, a polypropylene oxide skeleton, a urethane skeleton, a polybutadiene skeleton, and a nitrile rubber skeleton in a part of the molecule.
[0029] [6]
[0030] The conductive resin composition according to any one of [1] to [5], wherein the content of the component (B) is 0.1 parts by mass or more and 20 parts by mass or less based on 100 parts by mass of the component (A).
[0031] 〔7〕
[0032] The conductive resin composition according to any one of [1] to [6], further comprising a solvent as the component (C).
[0033] [8]
[0034] The conductive resin composition according to any one of [1] to [7], further comprising a curing agent as the component (D).
[0035] 〔9〕
[0036] The conductive resin composition according to [8], wherein the component (D) comprises at least one selected from the group consisting of an acid anhydride curing agent, a phenolic curing agent, and an amine curing agent.
[0037] 〔10〕
[0038] The conductive resin composition according to [8] or [9], further comprising a curing accelerator as the component (E).
[0039]
[11]
[0040] The conductive resin composition according to any one of [1] to
[10] , further comprising carbon particles as the component (G).
[0041]
[12]
[0042] The conductive resin composition according to
[11] , wherein the average particle size of the component (G) is 0.1 to 10 μm.
[0043] 〔13〕
[0044] The conductive resin composition according to
[11] or
[12] , wherein the content of the component (G) is 1 to 50 parts by mass based on 100 parts by mass of the component (A).
[0045]
[14]
[0046] The conductive resin composition according to
[10] , wherein the maximum value of the exothermic peak in the spectrum of differential scanning calorimetry of the composition containing the component (B), the component (D) and the component (E) is in the range of 175 to 250°C.
[0047] 〔15〕
[0048] The conductive resin composition according to any one of [1] to
[14] , wherein the viscosity at 25°C and 10 rpm is 10 to 10000 mPa·s.
[0049]
[16]
[0050] The conductive resin composition according to any one of [1] to
[15] , wherein the conductive resin composition is for spray coating.
[0051]
[17]
[0052] The conductive resin composition according to any one of [1] to
[15] , wherein the conductive resin composition is a spray coating agent for electromagnetic shielding.
[0053]
[18]
[0054] An electromagnetic wave shielding layer formed from the conductive resin composition described in any one of [1] to
[17] .
[0055]
[19]
[0056] An electronic component comprising the electromagnetic wave shielding layer described in
[18] .
[0057] Effects of the Invention
[0058] According to the present invention, it is possible to provide a conductive resin composition that can form an electromagnetic shielding layer having a high electromagnetic shielding effect and excellent adhesion after a reliability test. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a diagram showing DSC spectra of compositions containing the (B) component, the (D) component, and the (E) component in Examples 1 and 2 of the conductive resin composition according to the embodiment of the present invention. DETAILED DESCRIPTION
[0060] Hereinafter, the conductive resin composition of the present disclosure will be described in detail. However, the following embodiments are examples for embodying the technical concept of the present invention, and the present invention is not limited to the following conductive resin composition.
[0061] <Conductive resin composition>
[0062] The conductive resin composition according to an embodiment of the present invention comprises silver-containing particles as component (A) and at least one of a thermosetting resin or a thermoplastic resin as component (B). The conductive resin composition according to an embodiment of the present invention has an indentation elastic modulus E obtained from a load-displacement curve obtained by a nanoindentation test in the following steps. IT It is 10~20GPa.
[0063] [step]
[0064] (1) A conductive resin composition was applied onto a slide glass and heated at 200° C. for 20 minutes to form a coating film having a thickness of 50 μm to obtain a test piece.
[0065] (2) A load was applied to the coating surface of the test piece obtained in (1) using a Bosch indenter for 10 seconds until the maximum load reached 200 mN, the maximum load was maintained for 10 seconds, and then the load was removed for 10 seconds. A nanoindentation test was performed under these conditions to obtain a load-displacement curve.
[0066] It should be noted that, in the embodiment of the present invention, the compression elastic modulus E IT It indicates the ratio of the stress when the Berkovich indenter is inserted to the strain in the compression direction.
[0067] By making the indentation elastic modulus E of the conductive resin composition according to the embodiment of the present invention measured by the above-mentioned specific procedure IT When the pressure is 10 to 20 GPa, the cured product (electromagnetic wave shielding layer) absorbs the internal stress generated by the difference in thermal linear expansion coefficient between the adherend and the cured product (electromagnetic wave shielding layer), thereby maintaining adhesion even after reliability testing in a high temperature and high humidity environment, thereby forming an electromagnetic wave shielding layer with excellent durability.
[0068] The indentation elastic modulus E of the conductive resin composition according to the embodiment of the present invention IT It needs to be 10 to 20 GPa. From the perspective of the adhesion of the electromagnetic wave shielding layer obtained by the conductive resin composition, it is preferably 12 GPa or more, and more preferably 14 GPa or more. In addition, from the perspective of the adhesion of the electromagnetic wave shielding layer obtained by the conductive resin composition, it is more preferably 18 GPa or less. IT , from the viewpoint of adhesion, it is more preferably 12 to 18 GPa, and particularly preferably 14 to 18 GPa.
[0069] The conductive resin composition according to the embodiment of the present invention may be used for spraying. The conductive resin composition according to the embodiment of the present invention may also be a spray agent for electromagnetic wave shielding. In addition, the conductive resin composition according to the embodiment of the present invention may be used to form an electromagnetic wave shielding layer.
[0070] (A) Ingredients (Silver-containing particles)
[0071] The conductive resin composition according to the embodiment of the present invention contains silver-containing particles as the component (A). The silver-containing particles are blended to shield electromagnetic waves.
[0072] The silver-containing particles (hereinafter sometimes referred to as "(A) component" or "(A) silver-containing particles") are not particularly limited and include silver particles such as silver powder, alloy particles containing silver, silver-coated particles in which non-silver particles such as carbon particles are coated with silver, and silver-coated particles in which single or alloy metal particles of ferromagnetic bodies such as nickel and iron are coated with silver.
[0073] (A) The silver-containing particles may be used alone or in combination of two or more.
[0074] In the embodiment of the present invention, the (A) silver-containing particles preferably include metal particles such as silver particles or alloy particles including silver, and more preferably include silver particles. This is because silver has a higher electrical conductivity than other metals. By including silver particles as the (A) silver-containing particles, a conductive resin composition having a higher electromagnetic wave shielding effect can be obtained.
[0075] Regarding the silver-containing particles, nano-scale silver particles are preferred from the viewpoint of sinterability and sprayability. The average particle size (D50) of the silver-containing particles is preferably 1000 nm or less, more preferably 500 nm or less, further preferably 350 nm or less, and particularly preferably 150 nm or less. In addition, it is preferably 50 nm or more, more preferably 80 nm or more, and further preferably 100 nm or more. Regarding the average particle size (D50) of the silver-containing particles, from the viewpoint of sinterability and sprayability, it is preferably 50 nm to 1000 nm, more preferably 80 nm to 500 nm, further preferably 100 nm to 350 nm, and particularly preferably 100 nm to 150 nm.
[0076] When the average particle size of the silver-containing particles is within the above range, the shielding layer becomes a dense film structure, thereby improving conductivity, and can be made into a conductive resin composition suitable for spraying. In the conductive resin composition of the embodiment of the present invention, it is preferred that the (A) component contains silver particles having an average particle size of 100 nm or more and 350 nm or less.
[0077] The average particle size of the (A) silver-containing particles can be measured, for example, by observation using a scanning electron microscope (SEM). For example, a SEM photograph or SEM image of the (A) silver-containing particles can be obtained at a magnification of 10,000 to 20,000 times, and the contour of the (A) silver-containing particles in the SEM photograph or SEM image can be approximated to a perfect circle, and the diameter of the perfect circle is measured, and the arithmetic mean of the diameters of any 50 (A) silver-containing particles is taken as the average particle size.
[0078] The shape of the (A) silver-containing particles is not particularly limited, and may be any shape such as spherical, granular, flaky, needle-like, or scaly.
[0079] When the silver-containing particles (A) are scaly or acicular in shape, the average value of the major axis of the scaly or acicular shape may be used as the average particle size. From the viewpoint of the viscosity and sprayability of the conductive resin composition, the silver-containing particles (A) are preferably spherical.
[0080] (A) The method for producing the silver-containing particles is not particularly limited, and the particles may be produced by, for example, a reduction method, a pulverization method, an electrolysis method, an atomization method, a heat treatment method, or a combination thereof. For example, the silver-containing particles may also be produced by these production methods. The flaky silver-containing particles may be produced, for example, by flattening spherical or granular silver-containing particles using a ball mill or the like.
[0081] Specifically, as the (A) silver-containing particles, silver powder (trade name: P620-7, P620-24) manufactured by Metalor Technologies USA, Inc., silver powder (trade name: Ag nano powder-2) manufactured by DOWA Electronics Co., Ltd., and the like can be used.
[0082] The (A) silver-containing particles are preferably contained in the conductive resin composition in an amount of 35% by mass or more and 99% by mass or less, in an amount of 40% by mass or more and 98% by mass or less, or in an amount of 45% by mass or more and 92% by mass or less, in terms of solid content. It should be noted that the so-called solid content conversion refers to the resin composition after removing volatile components such as solvents.
[0083] The (A) silver-containing particles can use a masterbatch that is pre-dispersed in the (C) solvent described later. The masterbatch is a material in which the (A) silver-containing particles are pre-dispersed in the (C) solvent to form a slurry. By using a masterbatch containing (A) silver-containing particles in the conductive resin composition, the shielding layer becomes a dense film structure, and the adhesion to the surface of the electronic component can be improved. In the case where the conductive resin composition further contains a solvent as the (C) component as described later, the (C) solvent can be added to the conductive resin composition in addition to the (C) solvent contained in the masterbatch.
[0084] Specifically, as the masterbatch, a paste containing silver particles manufactured by DOWA Electronics Co., Ltd. (trade name: nanoAg (SNM-007 (NET92%)) or the like can be used.
[0085] (B) Component (thermosetting resin or thermoplastic resin)
[0086] The conductive resin composition according to the embodiment of the present invention contains at least one selected from a thermosetting resin and a thermoplastic resin as the component (B) (hereinafter sometimes referred to as “component (B)” or “resin (B)”).
[0087] The (B) resin imparts adhesion and curability to the conductive resin composition. Both thermosetting resins and thermoplastic resins may be included as the (B) resin. The content of the (B) resin is preferably in the range of 0.1 to 20 parts by mass, more preferably in the range of 1 to 10 parts by mass, further preferably in the range of 1.5 to 8 parts by mass, and particularly preferably in the range of 2 to 7 parts by mass, relative to 100 parts by mass of the (A) silver-containing particles. If the content of the (B) resin is in the range of 0.1 to 20 parts by mass relative to 100 parts by mass of the (A) silver-containing particles, the conductive resin composition covers the entire object closely, and it is easy to form a roughly uniform electromagnetic wave shielding layer.
[0088] The (B) resin may be at least one selected from a thermosetting resin or a thermoplastic resin. From the viewpoint of adhesion and curability, the (B) resin is preferably contained in the conductive resin composition in a range of 0.5 mass % to 10 mass %, and may be contained in a range of 0.8 mass % to 4.8 mass %.
[0089] The (B) resin contained in the conductive resin composition preferably includes a thermosetting resin. Examples of the thermosetting resin include epoxy resins. That is, in the conductive resin composition according to the embodiment of the present invention, it is preferred that the (B) component includes an epoxy resin.
[0090] The thermosetting resin may be used alone or in combination of two or more.
[0091] The epoxy resin preferably has at least one epoxy group or glycidyl group in the molecule and is liquid at room temperature.
[0092] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene epoxy resin, hydrogenated bisphenol epoxy resin, alicyclic epoxy resin, alcohol ether epoxy resin, cycloaliphatic epoxy resin, fluorene epoxy resin, siloxane epoxy resin, aminophenol epoxy resin and cresol novolac epoxy resin.
[0093] In addition, regarding the epoxy equivalent, from the viewpoint of curability and elastic modulus of the cured product, it is preferably 100 to 400 g / eq, and more preferably 180 to 350 g / eq. By making the epoxy equivalent within this range to control the curability of the resin, the adhesion with the adherend is improved, and it is easy to take into account both electrical conductivity and shielding properties. If the epoxy equivalent of the epoxy resin is above 100 g / eq, the amount of polar reactive groups is sufficient, the adhesion with the metal is improved, and the curing speed of the resin is accelerated, so that the curing of the resin can be prevented from hindering the sintering of the silver-containing particles and / or the formation of the conductive path of the silver-containing particles. On the other hand, if the epoxy equivalent is below 400 g / eq, the reactivity of the epoxy resin is excellent, the conductivity and shielding properties are improved, and even if the curing of the resin is insufficient, the reduction of adhesion and durability can be suppressed.
[0094] The component (B) preferably contains an epoxy resin having a flexible skeleton. The epoxy resin may be an epoxy resin having a flexible skeleton (epoxy resin having a flexible skeleton), and the conductive resin composition may contain an epoxy resin having a flexible skeleton as the resin (B).
[0095] When the conductive resin composition contains an epoxy resin having a flexible skeleton as the resin (B), the flexibility of the coating film formed from the conductive resin composition is increased, and the indentation elastic modulus E is easily increased. IT The epoxy resin having a flexible skeleton may be contained in the resin (B) as a main component.
[0096] More specifically, as the epoxy resin having a soft skeleton, it is preferred that the epoxy resin has two or more epoxy groups in one molecule and contains at least one soft skeleton selected from a polyoxyalkylene skeleton, a polyethylene glycol skeleton, a polypropylene glycol skeleton, a polyether skeleton, a polypropylene oxide skeleton, a urethane skeleton, a polybutadiene skeleton, and a nitrile rubber skeleton in a part of the molecule. By setting the epoxy resin having a soft skeleton to have two or more epoxy groups in one molecule and containing at least one soft skeleton selected from a polyoxyalkylene skeleton, a polyethylene glycol skeleton, a polypropylene glycol skeleton, a polyether skeleton, a polypropylene oxide skeleton, a urethane skeleton, a polybutadiene skeleton, and a nitrile rubber skeleton in a part of the molecule, the softness of the coating film is increased when the conductive resin composition is used to form the coating film, and it is easy to make the indentation elastic modulus E IT for a specific range.
[0097] Among them, from the viewpoint of having more excellent water resistance (hydrolysis resistance), it is preferable to use an epoxy resin including at least one flexible skeleton selected from a polypropylene oxide skeleton, a urethane skeleton, and a polybutadiene skeleton.
[0098] The entire main component may contain a component that does not have a flexible skeleton, such as bisphenol A epoxy resin or bisphenol F epoxy resin, but the compression elastic modulus E IT From the perspective of a specific range, these components are preferably set to 50% by mass or less of the entire main agent, and among them, the proportion of the epoxy resin component with a soft skeleton is preferably high, and the epoxy resin with a soft skeleton is preferably 50% by mass or more relative to the total amount of the epoxy resin, more preferably 90% by mass or more, and further preferably 100% by mass.
[0099] When the epoxy resin has a soft skeleton, it is easy to adjust the indentation elastic modulus of the conductive resin composition to a specific range, and this contributes to improving the adhesion of the electromagnetic wave shielding layer formed of the conductive resin composition.
[0100] Examples of commercially available epoxy resins include bisphenol F type epoxy resin (trade name: YDF8170) manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd., bisphenol A type epoxy resin (trade name: EXA-850CRP) manufactured by DIC Corporation, bisphenol A type bisphenol F type hybrid epoxy resin (trade name: EXA-835LV) manufactured by DIC Corporation, aminophenol type epoxy resin (grade: JER630) manufactured by Mitsubishi Chemical Corporation, cresol novolac type epoxy resin (trade name: EPICLON N665-EXP) manufactured by DIC Corporation, polypropylene oxide modified epoxy resin (trade name: EP4010S) manufactured by Adeka Corporation, polybutadiene skeleton-containing epoxy resin (trade name: PB3600) manufactured by Daicel Corporation, and urethane skeleton-containing epoxy resin (trade name: EPU-100) manufactured by Adeka Corporation. 7N) etc.
[0101] The (B) resin contained in the conductive resin composition may include a thermoplastic resin. When the (B) resin contained in the conductive resin composition includes a thermoplastic resin, the thermoplastic resin may include, for example, at least one selected from polystyrene resins, acrylic resins, polycarbonate resins, polyamide resins, polyamide-imide resins, and thermoplastic elastomers having a glass transition temperature of 25° C. or less and soluble in a liquid or organic solvent.
[0102] The acrylic resin is not particularly limited, and examples thereof include polymers obtained by polymerizing one or more monomers selected from acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters. A preferred acrylic resin is a polymer obtained by polymerizing acrylic acid or methacrylic acid.
[0103] The polycarbonate resin is not particularly limited, and a polymer obtained by a phosgene method in which a dihydroxydiaryl compound is reacted with phosgene or an ester exchange method in which a dihydroxydiaryl compound is reacted with a carbonate such as diphenyl carbonate can be used.
[0104] The polyamide resin is not particularly limited, and is a polymer containing an amide bond (-NH-CO-) in the main chain of the polymer, and examples thereof include 6 nylon, 66 nylon, copolymer nylon, and modified nylon such as N-methoxymethylated nylon.
[0105] The polyamide-imide resin is not particularly limited, and examples thereof include resins obtained by mixing tricarboxylic anhydride and a diamine compound or diisocyanate and then polycondensing the mixture.
[0106] Examples of the liquid thermoplastic elastomer having a glass transition temperature of 25° C. or less and dissolved in a liquid or organic solvent include acrylic rubber, butadiene rubber, silicone rubber, nitrile rubber, etc. As the thermoplastic elastomer, a commercially available product produced by a known method can be used, and examples of the commercially available product include carboxyl-terminated nitrile rubber (trade name: HYPRO CTBN 1300×13) manufactured by HUNTSMAN Co., Ltd.
[0107] (C) Component (Solvent)
[0108] The conductive resin composition according to an embodiment of the present invention may further contain a solvent as the component (C) (hereinafter sometimes referred to as "component (C)" or "solvent (C)".). By including the solvent (C) in the conductive resin composition, the viscosity of the silver-containing particles can be appropriately adjusted to improve the sprayability, and the cured film can be thinned by volatilizing the solvent during curing. In addition, the solvent (C) can be used as a solvent for preparing a masterbatch.
[0109] The (C) solvent of the conductive resin composition according to the embodiment of the present invention may be one kind of (C) solvent, or may contain two or more kinds of (C) solvents.
[0110] As the solvent (C), for example, at least one selected from the group consisting of terpinene, alkoxysilane, limonene, ethylene glycol monophenyl ether (EPH), diethylene glycol monobutyl ether acetate (butyl carbitol acetate: registered trademark), and diethylene glycol monobutyl ether (butyl carbitol: registered trademark) can be used. After the master batch is prepared, the solvent (C) may be further blended to adjust the viscosity of the conductive resin composition.
[0111] As the solvent (C), specifically, siloxane alkoxysilane (trade name: KBM103) manufactured by Shin-Etsu Silicon Co., Ltd. and ethylene glycol monophenyl ether (trade name: HISOLVE EPH) manufactured by Toho Chemical Industry Co., Ltd. can be used. The solvent (C) contained in the masterbatch containing the (A) silver-containing particles may be contained in an amount that suppresses the sedimentation of the (A) silver-containing particles and can maintain the slurry state.
[0112] The (C) solvent is preferably contained in the conductive resin composition in an amount of 5 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles. By containing the (C) solvent in an amount of 5 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles in the conductive resin composition, a shielding layer can be formed by spray coating, and a shielding layer having an electromagnetic wave shielding effect can be formed by volatilizing the (C) solvent. The amount of the (C) solvent contained in the conductive resin composition is preferably in the range of 6 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles, more preferably in the range of 7 parts by mass or more and 50 parts by mass or less, and particularly preferably in the range of 8 parts by mass or more and 30 parts by mass or less. When the masterbatch containing the (A) silver-containing particles contains the (C) solvent, the content of the (C) solvent in the conductive resin composition using the masterbatch may be in the range of 4 parts by mass or more and 100 parts by mass or less, 5 parts by mass or more and 80 parts by mass or less, 6 parts by mass or more and 70 parts by mass or less, or 7 parts by mass or more and 25 parts by mass or less, relative to 100 parts by mass of the (A) silver-containing particles in the conductive resin composition.
[0113] (D) Component (curing agent)
[0114] The conductive resin composition according to the embodiment of the present invention may further contain a curing agent as the component (D) (hereinafter, sometimes referred to as “component (D)” or “curing agent (D)”).
[0115] When the (B) resin includes a thermosetting resin, the conductive resin composition preferably further includes a (D) curing agent. That is, in the conductive resin composition, the (B) resin preferably includes a thermosetting resin and further includes a (D) curing agent. As the (D) curing agent, it is preferred that at least one selected from an acid anhydride curing agent, a phenolic curing agent, an amine curing agent, and an imidazole curing agent is included, and it is more preferred that at least one selected from an acid anhydride curing agent, a phenolic curing agent, and an amine curing agent is included, and it is further preferred that a phenolic curing agent is included. The (D) curing agent may be used alone or in combination of two or more. At least one (D) curing agent may be used as the (D) curing agent, and another may be used as the (E) curing accelerator described later.
[0116] Examples of the acid anhydride curing agent include phthalic anhydride, maleic anhydride, dodecenyl succinic anhydride, trimellitic anhydride, benzophenonetetracarboxylic dianhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, and hexahydrophthalic anhydride. Examples of commercially available products include tetrahydrophthalic anhydride (grade: HN2000) manufactured by Hitachi Chemical Co., Ltd., hexahydrophthalic anhydride (grade: HN5500) manufactured by Hitachi Chemical Co., Ltd., and acid anhydrides (grades: YH306 and YH307) manufactured by Mitsubishi Chemical Corporation.
[0117] As the phenolic curing agent, a phenol resin can be exemplified. As the phenol resin, any monomer, oligomer, or polymer having two or more phenolic hydroxyl groups that can react with the epoxy resin can be used.
[0118] In addition, the phenolic curing agent is preferably a liquid phenolic curing agent (liquid phenolic resin). It is believed that by using a liquid phenolic resin as the (D) curing agent, the curing start temperature is shifted to the high temperature side, the solvent in the cured product after the conductive resin composition is cured is easily removed, the coating film defects such as voids are reduced, and the adhesion is improved.
[0119] Examples of the phenolic resin include resol-type phenolic resins, phenol novolac resins, cresol novolac resins, bisphenol A-type novolac resins, and triazine-modified phenol novolac resins. Examples of commercially available products include novolac-type phenolic resins (trade name: RESITOP PSM4324) manufactured by Gunei Chemical Co., Ltd. and liquid phenolic resins (trade name: XPL4437E) manufactured by Gunei Chemical Co., Ltd.
[0120] Examples of the amine curing agent include aliphatic polyamines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, trimethylhexamethylenediamine, and 2-methylpentamethylenediamine; alicyclic polyamines such as isophoronediamine, 1,3-diaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornenediamine, and 1,2-diaminocyclohexane; piperazine-type polyamines such as N-aminoethylpiperazine and 1,4-bis(2-amino-2-methylpropyl)piperazine; and aromatic polyamines such as diaminodiphenylmethane, metaphenylenediamine, metaphenylenediamine, diaminodiphenyl sulfone, diethyltoluenediamine, trimethylenebis(4-aminobenzoate), and polytetramethylene ether glycol-di-p-aminobenzoate. Examples of commercially available products include 3,3′-diethyl-4,4′-diaminodiphenylmethane (trade name: KAYAHARD AA (HDAA)) manufactured by Nippon Kayaku Co., Ltd. and aromatic amine (trade name: ETACURE 100) manufactured by Albemarle Japan Co., Ltd.
[0121] As imidazole curing agents, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, etc. can be mentioned. Modified imidazole curing agents can also be used. As specific examples, epoxy-imidazole addition compounds and acrylate-imidazole addition compounds can be mentioned. As commercially available products, acrylate-imidazole addition compounds (trade name: EH2021) manufactured by ADEKA Co., Ltd. can be mentioned.
[0122] When an epoxy resin is used as the resin (B), the amount of the (D) curing agent varies depending on the type of the epoxy resin and the type of the (D) curing agent. The appropriate amount of the (D) curing agent is described below depending on the type of the (D) curing agent.
[0123] When the (D) curing agent is an acid anhydride curing agent, it is preferably blended so that the ratio of the acid anhydride equivalent (g / eq) of the (D) curing agent to the epoxy equivalent (g / eq) of the epoxy resin (acid anhydride equivalent / epoxy equivalent) is preferably 0.05 to 10, more preferably 0.1 to 5, and even more preferably 0.5 to 3.
[0124] When the (D) curing agent is a phenolic curing agent, it is preferably blended so that the ratio of the hydroxyl equivalent (g / eq) of the phenolic curing agent to the epoxy equivalent (g / eq) of the epoxy resin (hydroxyl equivalent / epoxy equivalent) is preferably 0.01 to 5, more preferably 0.04 to 1.5, and even more preferably 0.06 to 1.2.
[0125] When the (D) curing agent is an amine curing agent, it is preferably blended so that the ratio of the amine value (mgKOH / g) of the amine curing agent to the epoxy equivalent (g / eq) of the epoxy resin (amine value / epoxy equivalent) is preferably 0.001 to 3, more preferably 0.01 to 2, and further preferably 0.05 to 1.5. Here, the amine value refers to the number of mg of potassium hydroxide equivalent to the mole of hydrochloric acid required to neutralize 1 g of the solid content of the amine curing agent.
[0126] When the (D) curing agent is an imidazole-based curing agent, the imidazole-based curing agent is preferably blended in an amount preferably in a range of 0.1 parts by mass to 50 parts by mass, more preferably in a range of 0.25 parts by mass to 30 parts by mass, and even more preferably in a range of 0.5 parts by mass to 20 parts by mass, relative to 100 parts by mass of the epoxy resin.
[0127] (E) Component (curing accelerator)
[0128] The conductive resin composition according to the embodiment of the present invention may further contain a curing accelerator as the component (E) (hereinafter, sometimes referred to as “component (E)” or “(E) curing accelerator”).
[0129] The curing accelerator is a substance blended to accelerate the curing of the thermosetting resin. When an epoxy resin is used as the (B) resin, for example, imidazoles, salts of triphenylphosphine or tetraphenylphosphine, etc. can be used.
[0130] Specifically, 2-phenyl-4-methyl-5-hydroxymethylimidazole (trade name: CURESOL 2P4MHZ-PW) manufactured by Shikoku Chemicals, Ltd., 2-ethyl-4-methylimidazole (trade name: 2E4MZ) manufactured by Shikoku Chemicals, Ltd., 2-phenyl-4-methylimidazole (trade name: 2P4MZ) manufactured by Shikoku Chemicals, Ltd., etc. can be used.
[0131] When the conductive resin composition of the embodiment of the present invention includes components (D) and (E), it is preferred that the maximum value of the exothermic peak in the spectrum (DSC spectrum) of the composition including components (B), (D) and (E) when subjected to differential scanning calorimetry (DSC: Differential Scanning Calorimetry) is in the range of 175 to 250°C. By setting the maximum value of the exothermic peak in the DSC spectrum to the range of 175 to 250°C, the effect of low resistance can be obtained. It can be inferred that this is because by setting the curing start temperature of the thermosetting resin to the high temperature side, the sintering of the silver-containing particles starts first and is not easily affected by the decrease in fluidity accompanying the curing reaction of the thermosetting resin. Therefore, the sintering of the silver-containing particles is promoted and the resistance value is easily reduced. In addition, it is believed that by setting the curing start temperature of the thermosetting resin to the high temperature side, it is easy to remove the solvent in the cured product after the conductive resin composition is cured, and coating defects such as voids are reduced, and the adhesion is improved.
[0132] (F) Ingredients (additives)
[0133] The conductive resin composition according to the embodiment of the present invention may further contain various additives as the (F) component (hereinafter, sometimes referred to as “(F) component” or “(F) additive”).
[0134] (F) As the additive, for example, a silane coupling agent, a defoaming agent, a dispersant, etc. may be mix|blended.
[0135] The silane coupling agent is a substance blended to improve the heat resistance and adhesive strength of the conductive resin composition, and various silane coupling agents such as epoxy, amino, vinyl, methacrylic, acrylic, and mercapto silane coupling agents can be used. Among them, epoxy silane coupling agents having an epoxy group and methacrylic silane coupling agents having a methacrylic group are preferred.
[0136] Specifically, an epoxy silane coupling agent (3-glycidoxypropyltrimethoxysilane) (trade name: KBM403) manufactured by Shin-Etsu Chemical, a methacrylic silane coupling agent (3-methacryloxypropyltrimethoxysilane) (trade name: KBM503) manufactured by Shin-Etsu Chemical, or the like can be used.
[0137] When a silane coupling agent is added, the amount is preferably in the range of 0.01 to 5 parts by mass, and more preferably in the range of 0.05 to 3 parts by mass, based on 100 parts by mass of the (A) silver-containing particles.
[0138] The defoaming agent is a substance blended in order to prevent the generation of bubbles in the conductive resin composition, and for example, an acrylic, silicone, or fluorinated silicone defoaming agent can be used.
[0139] Specifically, a silicone-based defoaming agent manufactured by Asahi Kasei Wacker Silicone (trade name: Wacker AF98 / 1000) or the like can be used.
[0140] When adding a defoaming agent, the defoaming agent may be added in an amount within a range of 0.001 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles.
[0141] The dispersant is preferably at least one selected from acrylic dispersants, phosphate dispersants, and polyfunctional ionic dispersants from the viewpoint of compatibility with other components. If the conductive resin composition contains a dispersant as the component (F), the dispersibility of the (A) silver-containing particles and other components in the conductive resin composition can be improved.
[0142] Examples of acrylic dispersants include polyisobutyl methacrylate. As for phosphate dispersants, as commercially available products, for example, BYK-145 manufactured by BYK Chemie Co., Ltd. Examples of polyfunctional ionic dispersants include SC1015F of the MALIALIM (registered trademark) series or the MALIALIM (registered trademark) SC series manufactured by NOF Corporation. The MALIALIM (registered trademark) series dispersants manufactured by NOF Corporation are polyfunctional comb-type dispersants having an ionic group in the main chain and a polyoxyalkylene chain in the graft chain.
[0143] When a dispersant is added, the dispersant may be added in an amount within a range of 0.001 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles.
[0144] By including a dispersant in the conductive resin composition in an amount of 0.5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles, the sedimentation of the (A) silver-containing particles can be suppressed, and the shielding layer can be formed in a state where the (A) silver-containing particles are substantially uniformly dispersed. The amount of the dispersant contained in the conductive resin composition is preferably in a range of 1 part by mass or more and 8 parts by mass or less, and more preferably in a range of 1.5 parts by mass or more and 7 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles.
[0145] As the component (F), a dispersant may be included in a masterbatch in which the (A) silver-containing particles are dispersed in a slurry state in advance. If a dispersant is included as the component (F) in the masterbatch, the sedimentation of the (A) silver-containing particles can be suppressed, so that the shielding layer is formed in a state where the (A) silver-containing particles are dispersed approximately uniformly. When the dispersant is included in the masterbatch, it is sufficient as long as the dispersant is included in the range of 0.5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the (A) silver-containing particles contained in the conductive resin composition.
[0146] The amount of the additive in the conductive resin composition is preferably in the range of 0.01 to 5 parts by mass, preferably in the range of 0.05 to 3 parts by mass, relative to 100 parts by mass of the conductive resin composition. When added to a masterbatch, the amount of the additive in the conductive resin composition to which the masterbatch is added may be in the range of 0.01 to 5 parts by mass, relative to 100 parts by mass of the conductive resin composition.
[0147] (G) Component (carbon particles)
[0148] The conductive resin composition according to an embodiment of the present invention may further contain carbon particles as the component (G). Examples of the types of carbon particles include carbon black, Ketjen black, acetylene black, carbon nanotubes, graphene, graphite, and fullerene. Graphene is preferred from the viewpoint of improving the toughness of the shielding layer after curing and improving the adhesion after reliability testing.
[0149] Graphene is a substance composed of pure carbon in which atoms are arranged in a hexagonal pattern in a tightly packed sheet with a thickness of one atom.
[0150] In the conductive resin composition of the embodiment of the present invention, the average particle size (D50) of the carbon particles is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm, and even more preferably 1 to 3 μm. By setting the average particle size of the component (G) to be within this range, a conductive resin composition can be prepared that imparts toughness to the shielding layer after curing and has good sprayability.
[0151] If carbon particles are included in the conductive resin composition, when the conductive resin composition is applied to an object to form an electromagnetic wave shielding layer, the toughness of the electromagnetic wave shielding layer can be improved, and the adhesion after the reliability test can be improved. Commercially available products of carbon particles include, for example, graphite (flake graphite) (trade name: CX3000) manufactured by Chuetsu Graphite Industry Co., Ltd., graphene powder (grade: XGnP-R10) manufactured by XGScience Co., Ltd., and graphene (trade name: GNH-XA) manufactured by Graphene Platform Co., Ltd.
[0152] The content of the component (G) is preferably 1 to 50 parts by mass, more preferably 3 to 30 parts by mass, and even more preferably 5 to 25 parts by mass, based on 100 parts by mass of the component (A) in the conductive resin composition.
[0153] When the conductive resin composition contains carbon particles within the above range, the toughness of the electromagnetic shielding layer can be improved without reducing the adhesion between the conductive resin composition and the object, and an electromagnetic shielding layer having a high electromagnetic shielding effect and excellent durability can be formed.
[0154] (Viscosity)
[0155] Regarding the viscosity of the conductive resin composition, for example, the viscosity measured at 25°C and a rotation speed of 10 rpm using a rotational viscometer (model: TVE-22H) manufactured by Toki Sangyo Co., Ltd. is preferably 10 mPa·s or more, more preferably 15 mPa·s or more, further preferably 20 mPa·s or more, further preferably 25 mPa·s or more, and particularly more preferably 30 mPa·s or more. In addition, the upper limit of the viscosity is preferably 10000 mPa·s or less, more preferably 5000 mPa·s or less, further preferably 1000 mPa·s or less, further preferably 900 mPa·s or less, and particularly more preferably 850 mPa·s or less. If the viscosity of the conductive resin composition measured at 25°C and 10 rpm is within the range of 10 mPa·s or more and 10000 mPa·s or less, it is possible to prepare a conductive resin composition that is easy to spray (spray) coat, and therefore it is preferred.
[0156] The viscosity of the conductive resin composition can be adjusted by changing the type and blending ratio of the (C) solvent.
[0157] It should be noted that the viscosity in the present invention is the viscosity at 25°C.
[0158] <Method for producing conductive resin composition>
[0159] The conductive resin composition can be produced, for example, by mixing (A) silver-containing particles, (B) resin, (C) solvent as needed, (D) curing agent as needed, (E) curing accelerator as needed, (F) additives as needed, and (G) carbon particles as needed, and stirring and mixing them using a known device. As a known device, for example, a Henschel mixer, a roll mill, a three-roll mill, etc. can be used. The components constituting the conductive resin composition can be simultaneously introduced into the device for mixing, or a part of them can be introduced into the device first for mixing, and then the remaining part can be introduced into the device for mixing.
[0160] <Masterbatch manufacturing method>
[0161] In an embodiment of the present invention, (A) silver-containing particles and (C) solvent may be stirred and mixed in advance to produce a slurry masterbatch for use in the production of a conductive resin composition. The masterbatch may contain a dispersant as component (F) and other additives as needed. The (A) silver-containing particles and (C) solvent contained in the masterbatch may be stirred and mixed using the aforementioned known apparatus.
[0162] <Coating method>
[0163] The conductive resin composition according to the embodiment of the present invention can be applied to form an electromagnetic wave shielding layer.
[0164] For example, the conductive resin composition can be sprayed (sprayed) onto electronic components, etc., to form an electromagnetic wave shielding layer on the outer surface of the electronic components, etc. In addition, the conductive resin composition can be applied to the electronic components using a conventionally known spray coating machine, etc. In addition, the conductive resin composition can also be filled into an aerosol can, etc. for coating. The thickness of the electromagnetic wave shielding layer formed by spraying the conductive resin composition onto the electronic component can be in the range of 0.5 μm or more and 30 μm or less, or in the range of 0.5 μm or more and 20 μm or less, or in the range of 0.5 μm or more and 10 μm or less.
[0165] <Electromagnetic wave shielding layer>
[0166] The electromagnetic wave shielding layer according to the embodiment of the present invention is an electromagnetic wave shielding layer formed using the above-mentioned conductive resin composition.
[0167] The electromagnetic wave shielding layer according to the embodiment of the present invention can be formed using the above-mentioned conductive resin composition, and is preferably formed by spraying using the conductive resin composition.
[0168] The electromagnetic wave shielding layer formed using the conductive resin composition according to the embodiment of the present invention has an excellent electromagnetic wave shielding effect and can therefore effectively shield electromagnetic waves.
[0169] The electromagnetic wave shielding layer according to the embodiment of the present invention has an electromagnetic wave shielding effect of 37 dB or more, preferably 50 dB or more, particularly preferably 60 dB or more.
[0170] The electromagnetic wave shielding effect can be measured in accordance with ASTM D4935.
[0171] Regarding the electromagnetic wave shielding layer of the embodiment of the present invention, from the viewpoint of the heat release of the component, the thermal conductivity is preferably 7W / mK or more, more preferably 14W / mK or more, and further preferably 16W / mK or more. It should be noted that in order to improve the thermal conductivity, it is possible to consider increasing the content of silver-containing particles or promoting the sintering of silver-containing particles by treating at high temperatures, but no matter which method will lead to the embrittlement of the coating, the adhesion may be reduced. Therefore, from the viewpoint of adhesion and the strength of the coating, the thermal conductivity is preferably 400W / mK or less, more preferably 100W / mK or less, and further preferably 40W / mK or less.
[0172] The thermal conductivity is a value measured at 25° C. using a flash analyzer LFA447 manufactured by NETZSCH. The specific heat used in the calculation can be measured by the DSC method using a differential scanning calorimeter DSC204F1 manufactured by NETZSCH, and the specific gravity of the cured product can be measured by the Archimedean method.
[0173] The electromagnetic shielding layer formed by the conductive resin composition of the embodiment of the present invention has a tape adhesion of 4B or more in the tape adhesion and reliability tests shown in the following examples. With such tape adhesion, the electromagnetic shielding layer formed on the outer surface of the electronic component is not easily peeled off.
[0174] <Electronic components>
[0175] An electronic component according to an embodiment of the present invention includes the electromagnetic wave shielding layer according to an embodiment of the present invention.
[0176] The conductive resin composition according to the embodiment of the present invention can be used by applying it to an electronic component by spraying, etc. The present invention also relates to an electronic component using the conductive resin composition.
[0177] Examples of electronic components using the conductive resin composition according to the embodiment of the present invention include power amplifiers, Wi-Fi / Bluetooth modules, flash memory, etc. used in electronic devices such as mobile phones, smart phones, notebook computers, and tablet terminals. When the conductive resin composition is used in the electronic components, the conductive resin composition may be applied to each electronic component and then mounted on a substrate. Alternatively, the conductive resin composition may be applied to each electronic component after it is mounted on a substrate.
[0178] Example
[0179] Hereinafter, the present invention will be specifically described using examples, but the present invention is not limited to these examples.
[0180] When producing the conductive resin compositions of Examples and Comparative Examples, the following raw materials were used.
[0181] (A) Silver-containing particles
[0182] A1: nanoAg (SNM-007 (NET92%)), spherical, average particle size 100 nm, BC (butyl carbitol) slurry, manufactured by DOWA Electronics Co., Ltd. (In Tables 1 and 2, the amount used is the value calculated by removing 8% by mass of diethylene glycol monobutyl ether (butyl carbitol: registered trademark) as a solvent from the nano-Ag slurry))
[0183] It should be noted that the average particle size of the (A) silver-containing particles is observed using a scanning electron microscope (SEM), 50 particles are randomly selected from SEM photographs or SEM images at a magnification of 10,000 to 20,000 times, the contour of each particle is approximated to a perfect circle, the diameter of the perfect circle is measured, and the arithmetic mean value is set as the average particle size. In the case where the (A) conductive filler is in the form of a thin sheet (scaly), the average value of the major axis of the randomly selected 50 particles is set as the average particle size.
[0184] (B) Resin
[0185] B1: AER9000 (polypropylene oxide modified epoxy resin), manufactured by Asahi Kasei Corporation, epoxy equivalent: 380 g / eq
[0186] B2: EP4010S (polypropylene oxide modified epoxy resin), manufactured by ADEKA Corporation, epoxy equivalent: 350 g / eq
[0187] B3: PB3600 (epoxy resin containing a polybutadiene skeleton), manufactured by Daicel Co., Ltd., epoxy equivalent: 199 g / eq
[0188] B4: EPU 7N (epoxy resin containing a urethane skeleton), manufactured by ADEKA Corporation, epoxy equivalent: 230 g / eq
[0189] B5: CTBN 1300×13 (CTBN (carboxyl-terminated nitrile rubber), manufactured by HUNTSMAN Co., Ltd.
[0190] B6: AK601 (bisphenol A epoxy resin), manufactured by Nippon Kayaku Co., Ltd.
[0191] (C) Solvent
[0192] C1: KBM 103, manufactured by Shin-Etsu SILICONE Co., Ltd.
[0193] C2: Terpinolene, manufactured by Nippon Terpene Chemical Co., Ltd.
[0194] C3: Butyl Carbitol
[0195] (D) Curing agent
[0196] D1: Hexahydrophthalic anhydride (HN5500), anhydride curing agent, manufactured by Hitachi Chemical Co., Ltd.
[0197] D2: XPL4437E, phenolic curing agent, manufactured by Gunei Chemical Co., Ltd.
[0198] (E) Curing accelerator
[0199] E1: 2E4MZ, 2-ethyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd.
[0200] E2: 2P4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.
[0201] (F) Additives
[0202] F1: MALIALIMSC1015F, high molecular weight polycarboxylic acid dispersant, manufactured by NOF Corporation
[0203] (G) Carbon particles
[0204] Graphene (GNH-XA), particle size 2.5 μm, manufactured by Graphene Platform Co., Ltd.
[0205] Examples 1 to 9, Comparative Examples 1 to 3
[0206] The conductive resin composition was prepared by mixing and dispersing the raw materials using a three-roll mill in the proportions shown in the following tables. The values of the components (A) to (G) shown in the tables and the total values are parts by mass. The values without units in the tables represent parts by mass.
[0207] <Viscosity>
[0208] The viscosity of each conductive resin composition of Examples and Comparative Examples was measured using a TVE-22H viscometer (1° 34' cone rotor, R24) manufactured by Toki Sangyo Co., Ltd. 1 ml of a sample was measured and the result was read after rotating at 10 rpm for 1 minute at 25°C.
[0209] <Resistivity value>
[0210] A 50 μm thick stencil with a 50 mm × 2 mm linear printed pattern was prepared on a flat alumina substrate, and each conductive resin composition of the example and the comparative example was printed as a sample. The alumina substrate printed with the sample was cured at 200° C. for 20 minutes, and the line resistance of the obtained cured product was measured using a digital multimeter. The sample film thickness was measured using a SURFCOM 1500 surface roughness meter manufactured by Tokyo Seimitsu, and the resistivity value was calculated.
[0211] <Tape Adhesion>
[0212] Each conductive resin composition of the examples and comparative examples was applied as a sample on an epoxy resin cured product to a film thickness of about 150 μm, and cured at 200° C. for 20 minutes. The obtained test piece was subjected to a cross-cut test according to the procedure of ASTM D3359-97 to evaluate the tape adhesion.
[0213] Specifically, a sample was coated on a flat plate of 10 mm × 10 mm in size, cured at 200°C × 20 minutes, and six cuts were made in the resulting cured product at 1 mm intervals in the longitudinal and transverse directions using a cutter to form 25 (5 mm × 5 mm) 1 mm × 1 mm grids. A tape was attached to the resulting test piece and peeled off using the method described in ASTM D3359-97. The peeling state was evaluated by calculating the ratio of the peeled area based on the number of peeled pieces within the total area of the 5 mm × 5 mm grid when peeling.
[0214] The tape adhesion of the peeled surface after the tape was peeled off was evaluated on a five-level scale of 1B to 5B. 5B or higher was evaluated as "excellent", 4B was evaluated as "good", and 3B to 0B was evaluated as "unacceptable".
[0215] 5B: Not stripped
[0216] 4B: The peeling area is less than 5% of the total area of 5mm×5mm grid
[0217] 3B: The peeling area is greater than 5% and less than 15% of the total area of the 5mm×5mm grid
[0218] 2B: The peeling area is greater than 15% and less than 35% of the total area of the 5mm×5mm grid
[0219] 1B: The peeling area is greater than 35% and less than 65% of the total area of the 5mm×5mm grid
[0220] 0B: The peeling area is greater than 65% of the total area of 5mm×5mm grid
[0221] <Reliability test>
[0222] Each conductive resin composition of the examples and comparative examples was applied as a sample on an epoxy resin cured product to a film thickness of about 150 μm, and cured at 200°C for 20 minutes. The obtained test piece was subjected to a HAST (High Accelerated Stress Test) test condition of 130°C / 85% RH for 24 hours, and the adhesion after the test was evaluated in the same manner as the cross-cut test in <Tape Adhesion>.
[0223] <Thermal conductivity>
[0224] Each conductive resin composition of the embodiment and the comparative example was coated on a 1 mm thick copper plate as a sample so that the film thickness after curing was 100 to 150 μm, and cured at 200°C for 20 minutes, and carbon spray was applied on the surface of the obtained cured product to prepare a test piece. The thermal conductivity of the prepared test piece at 25°C was measured using a LFA447 flash analyzer manufactured by NETZSCH. The specific heat used in the calculation was measured by the DSC method using a differential scanning calorimeter DSC204F1 manufactured by NETZSCH, and the specific gravity of the cured product was measured by the Archimedean method.
[0225] <Indentation elastic modulus>
[0226] Each conductive resin composition of the embodiment and the comparative example is applied on a glass slide as a sample so that the film thickness of the cured film is 50 μm, and it is cured at 200°C × 20 minutes to produce a test piece (cured product). The measurement is carried out using a nanoindentation tester, ENT-NEXUS, manufactured by Elionix. For the test piece cured at 200°C × 20 minutes like this, a load of 200 mN is applied with a Bosch indenter for 10 seconds, the load is maintained for 10 seconds, and the load is unloaded for 10 seconds. The indentation depth is set to about 5 μm, which is about 1 / 10 of the sample film thickness of 50 μm, and the measurement is carried out in an area not affected by the glass slide.
[0227] Under these conditions, a nanoindentation test was performed to obtain a load-displacement curve. The indentation elastic modulus E defined in ISO14577 was calculated based on the obtained load-displacement curve. IT .
[0228] <Electromagnetic wave shielding effect>
[0229] The electromagnetic shielding effect was measured in accordance with ASTM D4935. A dispensing valve (DJ-2200, manufactured by Nordson ASYMTEK) was installed on a precision dispensing device (S2-920P manufactured by Nordson ASYMTEK), and the sample was applied to a polyimide substrate (thickness 1 mm) so that the film thickness after curing was 15 μm. The test piece was heated at 200°C for 20 minutes to produce the test piece. The test piece was measured using the "Coaxial Tube Type Shielding Effect Measurement System (500MHz~18Ghz)" manufactured by Keycom.
[0230] When the electromagnetic shielding effect was 50 dB or more, it was evaluated as “◎ (excellent)”, when it was 30 dB or more and less than 50 dB, it was evaluated as “○ (good)”, and when it was less than 30 dB, it was evaluated as “△ (pass)”.
[0231] <Sprayability>
[0232] A dispensing valve (trade name: jet dispensing valve, model: DJ-2200, manufactured by Nordson ASYMTEK) was installed on a precision dispensing device (trade name: SPECTRUM II dispensing machine, model: S2-920P, manufactured by Nordson ASYMTEK), and each conductive resin composition of the embodiment and comparative example was sprayed onto a flat surface. At this time, a needle with a nozzle diameter of 24G was used, and the nozzle clogging, spray interruption, scratches, etc. of the needle were evaluated. The state of being sprayed and applied in a straight line due to spraying was evaluated as "0 (good)", and the state of not being sprayed or being interrupted in the middle of a straight line due to spraying was evaluated as "× (inadequate)".
[0233] The conductive resin compositions of the examples and comparative examples and the evaluation results are shown in Tables 1 and 2. The compositions containing the components (B), (D) and (E) of Examples 1 and 2 were cured at 200° C. for 20 minutes, and the resulting cured products were measured using a differential scanning calorimeter DSC204F1 manufactured by NETZSCH. The resulting DSC spectra (resin-based DSC) are shown in Tables 1 and 2. Figure 1 middle.
[0234]
[0235]
[0236] As shown in Tables 1 and 2, the conductive resin compositions of Examples 1 to 9 are conductive resin compositions comprising (A) silver-containing particles and (B) a resin, and the compression modulus of elasticity EIT Since the pressure is in the range of 10 to 20 GPa, when the conductive resin composition is applied by spray coating, a coating film having high adhesion to an object such as an electronic component can be formed, and an excellent electromagnetic wave shielding effect can be obtained.
[0237] In addition, compared with Example 1, Example 2 uses phenolic resin as a curing agent, and thus shows excellent results in terms of adhesion after the reliability test. Figure 1 As shown in the DSC spectrum (resin-based DSC), by using a liquid phenolic resin as the (D) curing agent, the curing start temperature is shifted to the high temperature side, making it easier to remove the solvent in the cured product after the conductive resin composition is cured, reducing coating defects such as voids and improving adhesion.
[0238] The conductive resin composition of Comparative Example 1 has a low elastic modulus E IT The result of the reliability test showed that the adhesion was reduced, and it was judged that sufficient adhesion could not be obtained over time under a high temperature and high humidity environment. This is considered to be because the (B) resin used in Comparative Example 1 lacked reactivity and was insufficiently cured, so the initial resistance value increased. In addition, it is considered that the thermal shrinkage caused by the heat of the reliability test in Comparative Example 1 was large, and peeling occurred in the adhesion test after the reliability test.
[0239] Indentation elastic modulus E of the conductive resin composition of Comparative Example 2 not containing the component (B) IT When the pressure is greater than 20 GPa, the adhesion and reliability are insufficient.
[0240] Indentation elastic modulus E of the conductive resin composition of Comparative Example 3 IT When the pressure is greater than 20 GPa, the reliability is not sufficient.
[0241] Industrial Applicability
[0242] The conductive resin composition of the embodiment of the present invention can be applied to electronic components by spraying (spraying) to form an electromagnetic wave shielding layer, and can be suitably used in electronic components such as power amplifiers, Wi-Fi / Bluetooth modules, and flash memories used in electronic devices such as mobile phones, smartphones, notebook computers, and tablet terminals.
[0243] While the present invention has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various changes and modifications can be made therein without departing from the spirit and scope of the present invention.
[0244] This application is based on the Japanese patent application (Japanese Patent Application No. 2022-110666) filed on July 8, 2022, the contents of which are incorporated herein by reference.
Claims
1. A conductive resin composition comprising silver-containing particles as component (A) and at least one of a thermosetting resin or a thermoplastic resin as component (B), The indentation elastic modulus E of the conductive resin composition obtained from a load-displacement curve obtained by a nanoindentation test in the following steps is: IT 10GPa~20GPa; [step] (1) A conductive resin composition was applied on a slide glass and heated at 200° C. for 20 minutes to form a coating film with a thickness of 50 μm to obtain a test piece; (2) A load was applied to the coating surface of the test piece obtained in (1) using a Bosch indenter for 10 seconds until the maximum load reached 200 mN, the maximum load was maintained for 10 seconds, and then the load was removed for 10 seconds. A nanoindentation test was performed under these conditions to obtain a load-displacement curve.
2. The conductive resin composition according to claim 1, wherein The component (A) includes silver particles having an average particle size of 100 nm to 350 nm.
3. The conductive resin composition according to claim 1 or 2, wherein The component (B) contains an epoxy resin.
4. The conductive resin composition according to any one of claims 1 to 3, wherein The component (B) includes an epoxy resin having a flexible skeleton.
5. The conductive resin composition according to claim 4, wherein The epoxy resin containing a flexible skeleton contains at least one flexible skeleton selected from a polyoxyalkylene skeleton, a polyethylene glycol skeleton, a polypropylene glycol skeleton, a polyether skeleton, a polypropylene oxide skeleton, a urethane skeleton, a polybutadiene skeleton, and a nitrile rubber skeleton in a part of a molecule.
6. The conductive resin composition according to any one of claims 1 to 5, wherein The content of the component (B) is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the component (A). 7 . The conductive resin composition according to claim 1 , further comprising a solvent as a component (C). 8 . The conductive resin composition according to claim 1 , further comprising a curing agent as component (D).
9. The conductive resin composition according to claim 8, wherein The component (D) includes at least one selected from an acid anhydride curing agent, a phenolic curing agent, and an amine curing agent. 10 . The conductive resin composition according to claim 8 , further comprising a curing accelerator as component (E). 11 . The conductive resin composition according to claim 1 , further comprising carbon particles as a component (G).
12. The conductive resin composition according to claim 11, wherein The average particle size of the component (G) is 0.1 μm to 10 μm.
13. The conductive resin composition according to claim 11 or 12, wherein The content of the component (G) is 1 to 50 parts by mass based on 100 parts by mass of the component (A).
14. The conductive resin composition according to claim 10, wherein When a composition comprising the component (B), the component (D), and the component (E) is subjected to differential scanning calorimetry, the maximum value of an exothermic peak in a spectrum is in the range of 175° C. to 250° C. 15 . The conductive resin composition according to claim 1 , wherein the viscosity at 25° C. and 10 rpm is 10 mPa·s to 10,000 mPa·s.
16. The conductive resin composition according to any one of claims 1 to 15, wherein The conductive resin composition is for spraying.
17. The conductive resin composition according to any one of claims 1 to 15, wherein The conductive resin composition is a spray agent for electromagnetic wave shielding. 18 . An electromagnetic wave shielding layer formed from the conductive resin composition according to claim 1 .
19. An electronic component comprising the electromagnetic wave shielding layer according to claim 18.
Citation Information
Patent Citations
Conductive materials and processes
JP2014529674A
Spray coating agent for electromagnetic wave shielding
JP2020143225A
Absorbent article
JP2022110666A